Effects of Helicopter Parenting on Tutoring Engagement and Continued Attendance at Cram Schools - Ho, Ya-Jiuan; Hong, Jon-Chao; Ye, Jian-Hong; Chen, Po-Hsi; Ma, Liang-Ping; Chang Lee, Yu-Ju (Frontiers in Psychology, 2022)
Attending cram school has long been a trend in ethnic Chinese culture areas, including Taiwan. Despite the fact that school reform policies have been implemented in Taiwan, cram schools have continued to prosper. Therefore, in this educational culture, how to achieve a good educational effect is also a topic worthy of discussion. However, whether students really engage in those tutoring programs provided by cram schools has seldom been studied. To address this gap, this study explored how parents’ hovering attitude toward life and coursework influences their children’s engagement in cram schools. This study targeted those students who attend English cram schools to test the correlates between two types of helicopter parenting, tutoring engagement and continued attendance at cram schools. A total of 320 questionnaires were sent out, and 300 were returned, giving an overall response rate of 93.75%. Excluding seven incomplete or invalid questionnaires, 293 valid questionnaires were received. The results of this study show that hovering behavior awareness is negatively related to cram school engagement, whereas cram school engagement is positively related to the intention to continue attending cram school. Moreover, the results imply that parents should alleviate their helicoptering behavior to enhance their children’s engagement in cram school tutoring programs.